REPESENTASI KRITIK SOSIAL PADA LAGU ”BAYAR BAYAR BAYAR” KARYA SUKATANI : ANALISIS SEMIOTIKA ROLAND BARTHES - Sri Anaila Syafa Nur Aini; Buddy Riyanto (Solidaritas, 2025)
The phenomenon of social criticism through music in Indonesia has gained increasing attention, especially after the song “Bayar Bayar Bayar” by Sukatani sparked public controversy for its lyrics highlighting illegal levies by rogue police officers. Beyond its function as entertainment, music also serves as a medium to express criticism against social injustice and abuse of power. This study aims to describe how social criticism is represented in the lyrics of “Bayar Bayar Bayar” using Roland Barthes' semiotic approach. The research employs a descriptive qualitative method with data analysis focusing on identifying denotative, connotative, and myth meanings embedded in each verse of the song. The findings reveal that, at the denotative level, the lyrics depict the reality of having to pay money in various public matters. Connotatively, the lyrics convey sharp criticism of illegal levies as a form of power abuse by law enforcement officers. At the myth level, the lyrics reflect the collective belief in society that “paying the police” is normal and an unofficial requirement to access public services. This study underscores the important role of music as a medium for social criticism and reveals how these meanings are constructed and interpreted by society through symbols and cultural context. Keywords: social criticism, Roland Barthes semiotics, Sukatani, illegal levies.